Побудова стратегій переслідування з використанням функцій Ляпунова - Пашко, С.В. (Проблеми програмування, 2017)
Розглядаються диференційні ігри переслідування, в яких кілька агентів доганяють одного. Критерієм виступає час захоплення цілі. Для відомої стратегії паралельного зближення описана функція, що задає максимальний час переслідування. Ця функція використовується як функція Ляпунова для побудови нової стратегії переслідування, що перевершує стратегію паралельного зближення в наступному сенсі. Максимальний час переслідування для побудованої стратегії не перевищує максимального часу для стратегії паралельного зближення; водночас існує значна кількість ігор, в яких максимальний час переслідування для нової стратегії виявляється меншим, ніж для стратегії паралельного зближення. Рассматриваются дифференциальные игры преследования, в которых несколько агентов догоняют одного. Критерием является время захвата цели. Для известной стратегии параллельного сближения описана функция, задающая максимальное время преследования. Эта функция используется как функция Ляпунова для построения новой стратегии преследования, которая превосходит стратегию параллельного сближения в следующем смысле. Максимальное время преследования для построенной стратегии не превосходит максимального времени для стратегии параллельного сближения; вместе с тем существует значительное количество игр, в которых максимальное время преследования для новой стратегии оказывается меньшим, чем для стратегии параллельного сближения. This paper is concerned with differential pursuit-evasion games, in which several agents chase one. The time of capture of a target is used as the criterion. The motion of agents is simple one, the velocities are piecewise-continuous. The function that specifies the maximal time of capture of the target for the well-known strategy of parallel approach is described. This function is used as a Lyapunov function for constructing the new chase strategy, which outperforms the strategy of parallel approach in the following sense. Maximal time of pursuit for the new strategy is not more than maximal time of pursuit for the strategy of parallel approach; at the same time there are many games, for which maximal time of pursuit for the new strategy is less than for the strategy of parallel approach. In case of pursuit-evasion game on a plane we find explicit form of Lyapunov function and calculate velocities of pursuers using the gradient of this function. Numerical examples show that such velocities of pursuers reduce the maximal time of pursuit. In case of pursuit-evasion game in a multidimensional Euclidean space, Lyapunov function is equal to an optimal value of an objective function of appropriate linear programming problem. The velocities of pursuers are calculated with using the gradient of this function.